A Systematic Review of Clinical Practice Guidelines for the Diagnosis and Management of Bronchiolitis. (6th October 2020) - Kirolos, Amir; Manti, Sara; Blacow, Rachel; Tse, Gabriel; Wilson, Thomas; Lister, Martin; Cunningham, Steve; Campbell, Alasdair; Nair, Harish; Reeves, Rachel M; Fernandes, Ricardo M; Campbell, Harry; et al.
Abstract: Background: Bronchiolitis is the leading cause of hospital admission for respiratory disease among infants aged <1 year. Clinical practice guidelines can benefit patients by reducing the performance of unnecessary tests, hospital admissions, and treatment with lack of a supportive evidence base. This review aimed to identify current clinical practice guidelines worldwide, appraise their methodological quality, and discuss variability across guidelines for the diagnosis and management of bronchiolitis. Methods: A systematic literature review of electronic databases EMBASE, Global Health, and Medline was performed. Manual searches of the gray literature, national pediatric society websites, and guideline-focused databases were performed, and select international experts were contacted to identify additional guidelines. The Appraisal of Guidelines for Research and Evaluation assessment tool was used by 2 independent reviewers to appraise each guideline. Results: Thirty-two clinical practice guidelines met the selection criteria. Quality assessment revealed significant shortcomings in a number of guidelines, including lack of systematic processes in formulating guidelines, failure to state conflicts of interest, and lack of consultation with families of affected children. There was widespread agreement about a number of aspects, such as avoidance of the use of unnecessary diagnostic tests, risk factors for severe disease, indicators for hospital admission, discharge criteria, and nosocomial infection control. However, there was variability, even within areas of consensus, over specific recommendations, such as variable thresholds for oxygen therapy. Guidelines showed significant variability in recommendations for the pharmacological management of bronchiolitis, with conflicting recommendations over whether use of nebulized epinephrine, hypertonic saline, or bronchodilators should be routinely trialled. Conclusions: Future guidelines should aim to be compliant with international standards for clinical guidelines to improve their quality and clarity and to promote their adoption into practice. Variable recommendations between guidelines may reflect the evolving evidence base for bronchiolitis management, and platforms should be created to understand this variability and promote evidence-based recommendations.